The effect of public accounting firm size, financial distress, institutional ownership, and management change on the auditor switching in manufacturing companies listed in Indonesia Stock Exchange - Dewi Sri Kistini; Joicenda Nahumury (Universitas Hayam Wuruk Perbanas, 2014)
The purpose of this study is to examine the effect of public accounting firm size, financial distress, institutional ownership, and management change on auditor switching in the manufacturing companies listed in Indonesia Stock Exchange (IDX) from 2007 to 2012. The total samples in this research are 294 companies selected by using purposive sampling method based on specific criteria. Data are collected using secondary data from manufacturing companies listed in Indonesia Stock Exchange. The hypothesis is analyzed with Logistic Regression using SPSS’s program 20.0 version for windows. The result of this research indicates that public accounting firm size has significanteffect on auditor switching, meanwhile financial distress, institutional ownership, and management change do not have significant effect on auditor switching.